Tea and depression - Klaus W. Lange; Yukiko Nakamura; Katharina M. Lange; Hui Zhao (Food Science and Human Wellness)
ABSTRACT: The available evidence, which derives from studies investigating mechanistic effects of tea, research on animal models as well as epidemiological studies and intervention trials in humans, suggests that compounds contained in tea may have the potential to aid in the prevention of depression or in its treatment as an addition to established therapies. A wide range of potentially antidepressive biological activities of tea components have been reported. However, the mechanisms of tea phytochemicals possibly capable of decreasing the risk of depressive symptoms are complex, multifaceted and not well understood. Potent pharmacological effects on circumscribed neurobiological systems may be produced not by individual tea components but rather by the synergistic action of various compounds on multiple pathophysiological mechanisms involved in depression. While epidemiological studies have generally demonstrated beneficial effects of tea consumption on mood and depressive symptoms, cross-sectional studies are unable to prove a cause-effect relationship. If positive effects on mood could be firmly established, tea drinking could support mental health. However, the moderate antidepressive effects observed in healthy people are not necessarily indicative of possible clinical effects in major depressive disorder. Randomized controlled intervention studies are needed to establish a causal relationship between bioactive compounds in tea and depression.